THE SCIENTIFIC PARADIGM OF ISLAMIC EDUCATION MANAGEMENT: PHENOMENOLOGY PERSPECTIVE - Philip Buckley; Irawan Irawan (Jurnal Pendidikan Islam, 2015)
This paper intends to explore the possibility that phenomenology can be used as one of the foundations of scientific epistemology of Islamic education management. Scientific management of Islamic education would not be sufficient if only positivistic approached scientifically. Behaviors that contain messages of moral, theological and ideological embraced by managers, implementers and users of Islamic educational institutions are very complicated. To be able to describe these phenomena with a reasonable and until the deeply meaning (eidos), so phenomenological approach is needed. This approach can be used as a basis in developing others the science of Islamic education management. The science of Islamic education management can have a number of scientific fields (The science of diniyyah, madrassas, Islamic schools, and Islamic higher education management) and gave birth to a number of expertise (administrative staff, headmaster and superintendent at the madrasah level).